Association between intake of fruits and vegetables by pesticide residue status and coronary heart disease risk. (November 2019) - Chiu, Yu-Han; Sandoval-Insausti, Helena; Ley, Sylvia H.; Bhupathiraju, Shilpa N.; Hauser, Russ; Rimm, Eric B.; Manson, JoAnn E.; Sun, Qi; Chavarro, Jorge E.
Abstract: Background: Fruit and vegetable (FV) intake is recommended for the prevention of coronary heart disease (CHD). FVs are also an important source of exposure to pesticide residues. Whether the relations of FV intake with CHD differ according to pesticide residue status is unknown. Objective: To examine the associations of high- and low-pesticide-residue FVs with the risk of CHD. Methods: We followed 145, 789 women and 24, 353 men free of cardiovascular disease and cancer (excluding non-melanoma skin cancer) at baseline and participating in three ongoing prospective cohorts: the Nurses' Health Study (NHS: 1998–2012), the NHS-II (1999–2013), and the Health Professionals Follow-up Study (HPFS: 1998–2012). FV intake was assessed via food frequency questionnaires. We categorized FVs as having high- or low-pesticide-residues using a validated method based on pesticide surveillance data from the US Department of Agriculture. Multivariable Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (95%CI) of CHD in relation to high- and low-pesticide-residue FV intake. Results: A total of 3707 incident CHD events were identified during 2, 241, 977 person-years of follow-up. In multivariable-adjusted models, a greater intake of low-pesticide-residue FVs was associated with a lower risk of CHD whereas high-pesticide-residue FV intake was unrelated to CHD risk. Specifically, compared with individuals consuming <1 serving/day of low-pesticide-residue FVs, those consuming ≥4 servings/day had 20% (95CI: 4%, 33%) lower risk of CHD. The corresponding HR (comparing ≥4 servings/day to <1 serving/day) for high-pesticide-residue FV intake and CHD was 0.97 (95%CI: 0.72, 1.30). Conclusions: Our data suggested exposure to pesticide residues through FV intake may modify some cardiovascular benefits of FV consumption. Further confirmation of these findings, especially using biomarkers for assessment of pesticide exposure, is needed. Highlights: Whether exposure to lower levels of pesticides has any deleterious effect on coronary heart disease (CHD) is unknown.